A Moderating Role for Gender in Racial/Ethnic Disparities in Alcohol Services Utilization: Results from the 2000 to 2010 National Alcohol Surveys. (17th July 2014) - Zemore, Sarah E.; Murphy, Ryan D.; Mulia, Nina; Gilbert, Paul A.; Martinez, Priscilla; Bond, Jason; Polcin, Douglas L.
<x xml:space="preserve">Abstract</x> Background Few nationally representative studies have examined racial/ethnic disparities in alcohol services utilization. Further, little is known about whether racial/ethnic disparities generalize across genders, and what factors account for these disparities. Thus, we aimed to describe the combined impact of race/ethnicity and gender on alcohol services utilization, and to explore the roles for social influence factors in explaining racial/ethnic and gender disparities. Methods Data were pooled across the 2000, 2005, and 2010 National Alcohol Surveys. Outcomes included lifetime utilization of any services, specialty alcohol treatment, and Alcoholics Anonymous. Social influence factors were assessed as lifetime social pressures (i.e., pressures from a partner, friends, and/or family), legal consequences, and work‐related consequences. Core analyses included only those with a lifetime alcohol use disorder (AUD). Results Analyses revealed a pattern of lower services utilization among Latinos and Blacks (vs. Whites) and women (vs. men); further, race‐by‐gender interactions revealed that Black–White differences were limited to women, and provided some evidence of stronger Latino–White disparities among women (vs. men). Illustrating these patterns, among women, only 2.5% of Latinas and 3.4% of Blacks with a lifetime AUD accessed specialty treatment, versus 6.7% of Whites; among men, corresponding figures were 6.8% for Latinos, 12.2% for Blacks, and 10.1% for Whites. Racial/ethnic differences were typically robust (or stronger) when controlling for demographics and AUD severity. Evidence did not support a role for measured social influence factors in racial/ethnic disparities, but did suggest that these factors contribute to gender disparities, particularly among Whites and Blacks. Conclusions Findings for substantial Latino–White and Black–White disparities, especially among women, highlight the need for continuing research on explanatory factors and the development of appropriate interventions. Meanwhile, our evidence for persistent gender disparities and for social influence factors as drivers of these disparities tentatively suggests a need for intensified outreach to female heavy drinkers.